Identification of RS9960767 at TCF4 gene in Malaysian schizophrenia and rheumatoid arhtritis patients: a preliminary study - Ab Rajab, Nur Syafawati; Salleh, Mohd Razali; Mohd Yassin, Mohd Azhar; Wan Ghazali, Wan Syamimee; A.Talib, Norlelawati; Wan Taib, Wan Rohani; Sulong, Sarina (2015)

(untitled)
Objectives: Mutation of a TCF4 gene was previously reported as the cause of Schizophrenia. As documented long ago, there were inverse relationship between Schizophrenia (SZ) and Rheumatoid Arthritis (RA). Aim of this study is to detect genetic associations of a Single Nucleotide Polymorphism (SNP), rs9960767 at TCF4 gene between both patients group with controls. Methods: A total of 3ml whole blood was obtained from 47 SZ patients, 47 RA patients and 48 controls. Genomic DNA was extracted and PCR amplification of the exon 18 of TCF4 gene was performed. The PCR amplicon was digested with AluI restriction enzyme for rapid genotyping of the SNP and followed with 3% gel electrophoresis. Single association was analyzed using online SHEsis software based on Hardy-Weinberg Equilibrium using Chi-square calculation with 95% confidence interval (CI) and P value <0.05 is considered statistically significant. Results: The incidence of the mutation allele among the patients were 3.2% in SZ and 2.1% in RA while compared to controls incidence are 3.1% (p=0.98, OR=0.978; %95 CI=0.193-4.98 between SZ and controls and p=0.67, OR=1.48;